The Impact of the Implementation of Job Loss Guarantee in Law Number 6 of 2023 on Social Protection and Welfare of Workers Affected by Termination of Employment - Rakrian Ajar Legowo; Ratih Damayanti (Faculty of Law, Universitas Negeri Semarang, 2025)
Termination of employment (PHK) is an event that has significant impacts on the welfare of workers, both economically, socially, and psychologically. In response to this challenge, the Indonesian government introduced the Job Loss Insurance (JKP) program through Law Number 6 of 2023 as a new social protection scheme for workers affected by termination. This study employs a normative legal method with statutory and conceptual approaches to analyze the effectiveness of JKP in providing post-termination protection. The results show that the JKP scheme offers more comprehensive protection compared to the previous provisions in Law Number 13 of 2003. In addition to financial benefits in the form of cash assistance for up to six months, JKP also provides access to job training and employment placement services. This program not only helps workers survive the transitional period but also enhances their employment opportunities and competitiveness in the labor market. The scheme is managed by the Workers Social Security Agency (BPJS Ketenagakerjaan) with funding support derived from the redistribution of contributions from the Work Accident Insurance (JKK) and Death Insurance (JKM) programs, along with subsidies from the state budget (APBN). The implementation of JKP encourages active participation from both workers and employers in the social security system, strengthens labor formalization, and improves corporate accountability. With its proactive and sustainable approach, JKP has the potential to become a strategic instrument in the reform of national labor protection and to reinforce the role of the state in realizing social welfare for all Indonesian workers.